(untitled) (Research, Society and Development, 2021)
Oil production, applied in various sectors of the economy, can trigger environmental impacts from marine spills and spills in exploration, transportation and storage, capable of destroying biomes. To remedy impacted areas, containment and cleaning barriers in a marine environment are used. Lignocellulosic fibers have a high capacity to absorb oil, and can easily serve as barriers in a spill process, preventing the oil stain from spreading, in addition to providing remediation of the impacted site. Sisal fiber is a lignocellulosic material and is found on a large scale in nature as a by-product of agricultural production in addition to being materials from renewable sources as well as biodegradable. The present work aims to carry out a study involving tests carried out in the laboratory in order to verify the efficiency of fresh sisal fiber in the sorption of oil in the Campos Basin. The morphological analysis of the fiber, through the Scanning Electron Microscope (SEM), allowed access to enlarged images of the surface area of the fiber, composed of pores responsible for the oil adsorption process. To assess its efficiency, offshore spill tests were simulated, under different periods (5, 20, 40, 60, 90 and 120 minutes), using the reciprocating table (126 rpm), which simulates marine hydrodynamics. The data collected suggested the need for a minimum time of 5 minutes of contact with oil in eventual marine spills. Fiber recycling was analyzed over six subsequent cycles. The adsorptive potential of the last cycle dropped approximately 12% from the first sorption, characterizing good fiber reuse after successive applications.